Nebulization for Mycoplasma Control in Goats - Enhancing the Therapeutic Efficacy of Tiamulin Fumarate - Cheng, Cheng (2024)
Background: Contagious caprine pleuropneumonia (CCPP) presents a significant peril to the well-being of goats, manifesting in clinical indications such as coughing, elevated body temperature, and the presence of fibrinous and serous inflammation in the pleura and lungs. Furthermore, it can give rise to secondary complications, including arthritis, urinary and reproductive tract infections, and mastitis. Tiamulin fumarate is a frequently employed pharmaceutical agent for the management of CCPP, exhibiting good therapeutic efficacy against Mycoplasma infection in goats. Presently, the predominant route of administration for tiamulin fumarate is through injection. Nevertheless, this approach possesses inherent constraints and fails to adequately address the exigencies of prompt treatment for goats harboring latent infections or displaying subclinical symptoms. Consequently, the optimization of drug administration methods has emerged as a crucial imperative in the realm of agricultural production. Materials, Methods & Results: A total of 15 goats naturally infected with Mycoplasma were selected and randomly divided into 3 groups. Group A received nebulization, Group B received intramuscular injection (IM) as the control, and Group C served as the blank control. Nasal swab samples were collected from the 3 groups of goats at 0, 7, and 15 days after the start of treatment. Quantitative real-time PCR was used to detect the intensity of Mycoplasma infection. The weight and clinical symptom changes of the goats in the 3 groups were recorded before and after treatment. The results showed that in Group A, the reduction rates of Mycoplasma infection intensity were recorded as 78.27% and 85.29% at both 7 and 15 days following the initiation of treatment compared to day 0. In Group B, the reduction rates of Mycoplasma infection intensity were calculated to be 76.39% and 80.60% at 7 and 15 days at both 7 and 15 days following the treatment compared to day 0. In Group C, the average intensity of Mycoplasma infection exhibited an increase at both 7 and 15 days in comparison to day 0. In Group A, the average weight gain rates of goats at 7, 15, and 30 days after the start of treatment were 5.64%, 14.11%, and 31.87% in comparison to day 0. These rates were better than those of Group B (5.20%, 11.20%, and 25.44%). The weight gain rates were also superior to those of Group C (5%, 9.54%, and 21.86%). All goats in Group A had their clinical symptoms disappear within 7 days of treatment, while in Group B, all goats had their clinical symptoms disappear within 15 days of treatment. However, in Group C, the clinical symptoms of goats showed no improvement within 30 days. Discussion: The study investigates the efficacy of nebulized tiamulin fumarate in treating 15 naturally infected goats with CCPP by employing quantitative methods in order to investigate changes in infection intensity, weight, and clinical symptoms following medication through nebulization and IM injection. The findings revealed that nebulization exhibits marginally superior therapeutic effects compared to intramuscular injection. Moreover, nebulized tiamulin fumarate has shown a more pronounced impact on promoting goat growth. Additionally, nebulization serves a preventive function for other goats within the same group while concurrently treating symptomatic goats. Keywords: tiamulin fumarate, therapeutic efficacy, nebulization, Mycoplasma sp., caprine, goats, CCPP.